Draft Annual Plan 1993-94 Vol-II Planning and Co-ordination Department Government of Tripura - Planning Commission (Planning Commission, 1993)
The economy of the State is basically agrarian and more than 70% of the population depends on Agriculture for their livelihood. Agriculture contributes a major share of the income of the State. As per 1981 Agri Census, 59.1% of the holding (1.95 lakh Hactre) is occupied by small and Marginal Fanners group having less than two hactares of land. the average size of holding is about 1.87 ha. out of total geographical area of the State which is 10.491 sq. kilo-mitre (10,49,169 hectare), only 27% area is undei- cultivation. There is not much scope to bring further area unaer cultivation without necessary relaxation of the provision of the central Forest Act.
Planning and Co-ordination Department Government of Tripura